2013
DOI: 10.1080/08957959.2013.833613
|View full text |Cite
|
Sign up to set email alerts
|

Novel high pressure monoclinic Fe2O3 polymorph revealed by single-crystal synchrotron X-ray diffraction studies

Abstract: A novel high pressure polymorph of iron sesquioxide, m-Fe 2 O 3 , has been identified by means of singlecrystal synchrotron X-ray diffraction (XRD). Upon compression of a single crystal of hematite, α-Fe 2 O 3 , in a diamond anvil cell, the transition occurs at pressure of about 54 GPa and results in ∼10% volume reduction. The crystal structure of the new phase was solved by the direct method (monoclinic space group P2 1 /n, a = 4.588(3), b = 4.945(2), c = 6.679(7) Å and β = 91.31(9) • ) and refined to R 1 ∼11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 40 publications
9
40
0
Order By: Relevance
“…On the other hand, the value of the quadratic elongation of the octahedral unit around Fe(3) is around 1.008 and remains almost unalterable with compression along the stability range of this phase. This parameter is quite similar to those observed in other polymorphs such as γ-Fe 2 O 3 (with λ equal to 1.0024 for the octahedron and 1.000 for the tetrahedron) 41 , the high pressure monoclinic-Fe 2 O 3 (with two out of the three octahedral units with a λ of 1.0025 and 1.0021, respectively) 42 , and ζ-Fe 2 O 3 (an octahedron with λ of 1.0109) 43 .
Fig. 3Analysis of the volume and the quadratic elongation of the polyhedral units under pressure.
…”
Section: Resultssupporting
confidence: 85%
“…On the other hand, the value of the quadratic elongation of the octahedral unit around Fe(3) is around 1.008 and remains almost unalterable with compression along the stability range of this phase. This parameter is quite similar to those observed in other polymorphs such as γ-Fe 2 O 3 (with λ equal to 1.0024 for the octahedron and 1.000 for the tetrahedron) 41 , the high pressure monoclinic-Fe 2 O 3 (with two out of the three octahedral units with a λ of 1.0025 and 1.0021, respectively) 42 , and ζ-Fe 2 O 3 (an octahedron with λ of 1.0109) 43 .
Fig. 3Analysis of the volume and the quadratic elongation of the polyhedral units under pressure.
…”
Section: Resultssupporting
confidence: 85%
“…For the novel monoclinic phase (space group P21/n) proposed by Bykova et al [20,21] at 54 GPa, only the expected average Fe-O distance is in agreement with that of EXAFS (Tab. I, 4th row); in contrast, the value of σ 2 indicates a small, but not negligible, Fe-O distortion and therefore we cannot validate this HP structure.…”
supporting
confidence: 73%
“…However this conclusion cannot be regarded as definitive because not based on x-ray "single-crystal" diffraction data, that provides the most accurate structural refinement, and moreover because certain aspects have been challenged by Badro and co-workers [2]. In confirmation of this, a recent synchrotron x-ray single-crystal diffraction study proposes that, in the mixed state above 50 GPa, Fe 2 O 3 forms a novel monoclinic phase with space group P2 1 /n and, above 67 GPa, compression triggers the transition to a different HP phase with orthorhombic unit cell and space group Aba2 [20,21]. Another important and controversial point refers to the nature of the phase-transition at ∼50 GPa: is it the structural transition that drives the electronic transition or viceversa?…”
mentioning
confidence: 80%
“…For instance, at room temperature cubic Fe 1-x O wüstite with the rocksalt structure transforms to a rhombohedral lattice above 20 GPa1, while at high temperatures the rocksalt structure of Fe 1-x O is stable to at least 60 GPa12. High temperature-assisted phase transitions in Fe 3 O 4 from cubic spinel to an orthorhombic phase3435, and from corundum-type α -Fe 2 O 3 to an orthorhombic Rh 2 O 3 (II)-type or to other phases45678 were also observed in some studies already above 20–25 GPa, although these phase transitions are still hotly debated. These observations suggest that all conventional iron oxides ( α -Fe 2 O 3 , Fe 3 O 4 , and Fe 1-x O) become unstable with respect to structural transformations in approximately similar pressure ranges that might be related to similar shortening of Fe-O bond lengths in their structures.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been devoted to investigations of various properties of iron oxides at conditions relevant to the Earth’s interior, i.e., at high pressure or at high pressure combined with high temperature (HP-HT). These studies reported a number of remarkable findings for the three basic iron oxides, Fe 1-x O wüstite12, α -Fe 2 O 3 hematite345678, and Fe 3 O 4 magnetite91011. Meanwhile, several experimental and theoretical studies indicated that the chemistry of iron oxides at extreme conditions of high pressure and high temperature may extend to intriguing behavior beyond these three well-known oxides12131415.…”
mentioning
confidence: 99%